Strengthening Foreign Reserve Exchange Through The Relationship Of Liquidity and Trade Variables: Evidence From Southeast Asian Selected Countries - Hanafi Arie Sunaryo (Ridwan Institute, 2023)
The recent years have witnessed intense debates on the enhancement of foreign exchange reserves' performance, yet the significance of this improvement for developing countries still needs to be answered. This study aims to investigate the connection and impact between money supply and exports on foreign exchange reserves in select Southeast Asian nations, namely Indonesia, Thailand, Malaysia, the Philippines, and Singapore. We utilised the Ordinary-Least Square (OLS) and Johansen Cointegration Test models to examine the effects of money supply and exports on foreign exchange reserves using annual data from 1990 to 2019 in these five ASEAN countries. Our findings indicate that, over the long term, money supply and exports exert a positive and substantial influence on the performance of foreign exchange reserves in these ASEAN countries. Our policy recommendation underscores the need for efforts aimed at bolstering foreign exchange reserves to prioritise the involvement of the respective governments in these selected ASEAN countries, both domestically and globally, through a series of collaborative initiatives designed to enhance foreign exchange reserves' performance.